Human Chromosomes - Miller, Orlando J.; Therman, Eeva (Springer, 2000)
This book presents a comprehensive introduction to the principles of human cytogenetics and provides examples of their applications, especially those that are important in diagnostic and preventive medicine. The authors have each worked in human cytogenetics for more than 40 years and have witnessed firsthand the enormous strides made in the field during this time . The many advances made since the third edition of this book reflect the rapidly growing application of molecular biological techniques and concepts by human cytogeneticists. Insertion of transposable elements, genomic imprinting, and expansion of trinucleotide repeats are only a few of the important cytogenetic mechanisms that have been discovered and shown to playa role in producing disease phenotypes. Molecular cytogenetic methods have taken center stage in cancer studies with the demonstration that cancers arise by chromosomal mechanisms such as gene amplification, oncogene activation by chromosome rearrangement, ectopic recombination leading to loss of heterozygosity, and multiple mechanisms leading to genome destabilization.
Keywords: Human chromosomes.; Human cytogenetics; Human chromosome abnormalities